2017
DOI: 10.1016/j.freeradbiomed.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic ascorbate induces neuroblastoma cell death by hydrogen peroxide mediated DNA damage and reduction in cancer cell glycolysis

Abstract: An ascorbate-mediated production of oxidative stress has been shown to retard tumor growth. Subsequent glycolysis inhibition has been suggested. Here, we further define the mechanisms relevant to this observation. Ascorbate was cytotoxic to human neuroblastoma cells through the production of H2O2, which led to ATP depletion, inhibited GAPDH, and non-apoptotic and non-autophagic cell death. The mechanism of cytotoxicity is different when PARP-dependent DNA repair machinery is active or inhibited. Ascorbate-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 56 publications
3
54
1
1
Order By: Relevance
“…Such a strategy could be applied to a variety of heterogeneous and hard-to-treat malignancies, including breast, pancreatic and prostate cancer, where BRCA1, BRCA2 or other HR repair proteins are instrumental in the repair of DNA DSBs and the potential of PARPis has not yet been fully exploited (39). Consistent with previous studies (22,29,40), the data in the present study demonstrated that treatment with pharmacological ascorbate resulted in the production of H 2 O 2 , which damages DNA, leading to PARP activation, and this was impaired by the PARPis. The oxidative stress induced by pharmacological ascorbate caused excessive DNA DSBs in BRCA1/2 wild-type EOC cells within the first 6 h of treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Such a strategy could be applied to a variety of heterogeneous and hard-to-treat malignancies, including breast, pancreatic and prostate cancer, where BRCA1, BRCA2 or other HR repair proteins are instrumental in the repair of DNA DSBs and the potential of PARPis has not yet been fully exploited (39). Consistent with previous studies (22,29,40), the data in the present study demonstrated that treatment with pharmacological ascorbate resulted in the production of H 2 O 2 , which damages DNA, leading to PARP activation, and this was impaired by the PARPis. The oxidative stress induced by pharmacological ascorbate caused excessive DNA DSBs in BRCA1/2 wild-type EOC cells within the first 6 h of treatment.…”
Section: Discussionsupporting
confidence: 93%
“…By generating H 2 O 2 , pharmacological ascorbate damages DNA and preferentially kills cancer cells (20,29). Therefore, it was hypothesized that the combination of pharmacological ascorbate and PARPis may enhance DNA repair deficiency, and thus enhance the therapeutic effect of either agent alone against EOC, regardless of BRCA status.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, there have been no benefits. However, new knowledge regarding the pharmacokinetic properties of Vit-C, and recent preclinical studies, have revived interest in the utilization of high-dose Vit-C for cancer treatment [132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Similar is the case of using IV Vit-C as antiviral, especially for the recent Covid19 [146][147][148][149][150].…”
Section: Discussionmentioning
confidence: 99%
“…The induction of the increase of intracellular RONS in cancer cells have been reported as a potential target for cancer therapies [17]. Many species are involved in the cellular effects of CAP; for instance, increased levels of hydrogen peroxide are well-known to induce double strand breaks, chromosomal fragmentation and apoptosis in cancer cells [18,19]. In addition, NO 2 − is a precursor for intracellular formation of NO, which induces protein and lipid oxidation, leading to cell death [20].…”
Section: Introductionmentioning
confidence: 99%